The use of pyloric exclusion for treating duodenal trauma: case series - Fraga, Gustavo Pereira (2008)
CONTEXT AND OBJECTIVES: Signifi cant controversy exists regarding the best surgical treatment for complex duodenal injuries. The aims of this study were to report on a series of eight cases of duodenal repairs using pyloric exclusion and to describe reported complications or improvements in clinical outcomes among patients with complex duodenal trauma. DESIGN AND SETTING: Cross-sectional study followed by a case series in a university hospital. METHODS: Data on eight patients with duodenal trauma who underwent pyloric exclusion over a 17.5 year period were collected and analyzed. RESULTS: The causes of the injuries included penetrating gunshot wounds (GSW) in fi ve patients and motor vehicle accidents (blunt trauma) in three patients. The time elapsed until surgery was longer in the blunt trauma group, while in one patient, the gunshot injury was initially missed and thus the procedure was carried out 36 hours after the original injury. The injuries were grade III (50%) or IV (50%) and the morbidity rate was 87.5%. Four patients (50%) died during the postoperative period from complications, including hypovolemic shock (one patient), sepsis (peritonitis following the missed injury) and pancreatitis with an anastomotic fi stula (two patients). CONCLUSIONS: Pyloric exclusion was associated with multiple complications and a high mortality rate. This surgical technique is indicated for rare cases of complex injury to the duodenum and the surgeon should be aware that treatment with a minimalistic approach, with only primary repair, may be ideal.